Paddy System with a Hybrid Rice Enhances Cyanobacteria Nostoc and Increases N2 Fixation - MA, Jing; BEI, Qicheng; WANG, Xiaojie; LIU, Gang; CADISCH, Georg; LIN, Xingwu; ZHU, Jianguo; SUN, Xiaoli; XIE, Zubin (Pedosphere, 2019)
Biological nitrogen (N) fixation (BNF) plays a significant role in maintaining soil fertility in paddy field ecosystems. Rice variety influences BNF, but how different rice varieties regulate BNF and associated diazotroph communities has not been quantified. Airtight, field-based 15N2-labelling growth chamber experiments were used to assess the BNF capacity of different rice varieties. In addition, both the 16S rRNA and nifH genes were sequenced to assess the influence of different rice varieties on bacterial and diazotrophic communities in paddy soils. After subjecting a rice-soil system to 74 d of continuous airtight, field-based 15N2 labelling in pots in a growth chamber, the amounts of fixed N were 22.3 and 38.9 kg ha–1 in inbred japonica (W23) and hybrid indica (IIY) rice cultivars planted in the rice-soil systems, respectively, and only 1%–2.5% of the fixed N was allocated to the rice plants and weeds. A greater abundance of diazotrophs was found in the surface soil (0–1 cm) under IIY than under W23. Sequencing of the 16S rRNA gene showed significantly greater abundances of the cyanobacterial genera Nostoc, Anabaena, and Cylindrospermum under IIY than under W23. Sequencing of the nifH gene also showed a significantly greater abundance of Nostoc under IIY than under W23. These results indicate that the hybrid rice cultivar (IIY) promoted BNF to a greater extent than the inbred rice cultivar (W23) and that the increase in BNF might have been due to the enhanced heterocystous cyanobacteria Nostoc.